La persona come risorsa fondamentale per lo sviluppo e anche per la citta’ - DOI: 10.5752/P.2316-1752.2009v16n18/19p215 - Morandè, Pedro (Cadernos de Arquitetura e Urbanismo, 2010)
Abstract About ten years ago, those in charge of public policies grew aware that unilateral welfare State generates a sort of paternalism that produces, in the most vulnerable population, dependence on the received aid. However, promoting the person’s autonomy as a key resource for his personal and social development is the task of society. Nevertheless, raising a critical awareness of welfarism is not enough, nor the desire to overcome it. Solidarity without subsidiarity regenerates welfarism. Key words : Welfarism; Critical awareness; Person; Subsidiarity.